SISTEM APLIKASI MONITORING RUANGAN BERBASIS WEBCAM - Sulistiyanto, Debby Wahyu; Basukesti, Agus; Retnowati, Nurcahyani Dewi (Compiler, 2013)
Software design and hardware application system monitoring room webcam based aims to add value to the webcam to be used as part of the security system, implementing the work process of hardware and software monitoring system formed using delphi 7, analyzing the performance o f a stepper motor as the driving platform webcam and documenting object images and sounds in the room activities into a file format AVI (Audio Video Interleave). Webcams are used in this design is equipped with a standard webcam lighting lamps LED (Light Emitting Diode) with a USB data line, while the driver controls the webcam in the design o f this platform using unipolar type stepper motor controlled by a microcontroller, motor drivers and line interface RS232 to USB (Universal Serial Bus) converter. The installation o f the webcam to webcam platform play will lead to the right, left, stop rotating right and or to the left automatically. From the test results it can be concluded that the monitoring system and webcam based indoor stepper motor consists o f webcam applications and motor control applications platform which is separately because both applications use the USB and COM communication channels are opened simultaneously. As for the results o f the motion setting webcam platform proved to have a consistent degree of deviation for the wine and left turn kenanan but still require a series o f additional gears for smooth movement o f the platform and to reduce the effects o f shadow on motion pictures.